Climate change and planktonic foraminiferal turnover during the Late Cretaceous - FALZONI, FRANCESCA; M.R. Petrizzo; L. J. Clarke; K. G. MacLeod; H. C. Jenkins (2017)
The ~35 myr-long Late Cretaceous greenhouse climate has been subjected to a number of studies with emphasis on the Cenomanian–Turonian and late Campanian–Maastrichtian intervals. By contrast, far less information is available for the Turonian–early Campanian, even though it encompasses the transition out of the extreme warmth of the Cenomanian–Turonian greenhouse climate optimum and includes a ~3 myr-long mid-Coniacian–mid-Santonian interval when planktonic foraminifera underwent a large-scale, but poorly understood, turnover. This variation in the assemblages was followed by the extinction of all pre-Campanian double-keeled taxa (Marginotruncana and Dicarinella) within the latest Santonian–earliest Campanian, whose cause(s) has/have never been established. This lack of understanding relates to the limited recovery of stratigraphically complete Turonian–early Campanian deep-sea records, as well as to the generally poor preservation of Turonian–lower Campanian microfossils from outcrop sections. Further uncertainty is introduced by the results of several studies that found the traditional morphology-based scheme for inferring Cretaceous planktonic foraminiferal paleoecology to be probably incorrect for many taxa (Abramovich et al., 2003; Ando et al., 2010; Falzoni et al., 2013). This study presents ~1350 δ18O and δ13C values of well-preserved benthic and planktonic foraminifera and of the <63 μm coccolith-rich size fraction from the Exmouth Plateau off Australia (eastern Indian Ocean – ODP Leg 122, Hole 762C). These data provide: (i) the most continuous, highly resolved and stratigraphically well-constrained record of long-term trends in Late Cretaceous oxygen- and carbon-isotope ratios from the southern mid-latitudes, and (ii) new information on the paleoecological preferences of planktonic foraminiferal taxa. The results indicate that the mid-Cretaceous climate optimum persisted until the mid-Santonian, while sea-surface cooling occurred from the mid-Santonian through the mid-Campanian, and short-term ...